Can exist social inclusion of disability people in the world of the work and the capitalist education? - Antonio Pereira (Universidade Federal de Santa Maria (UFSM), 2008)
This text makes a critical analysis, in the marxist perspective, of the process of social inclusion of carrying people of necessities special, having as deep cloth of the current world of the work and the education. One searchs to evidence briefly, despite, the symptoms that corrective delinquents do not allow that the capitalist system makes the inclusion, only, as Mészáros signals.